Alpha-2 nicotinic acetylcholine receptors regulate spectral integration in auditory cortex - Intskirveli, Irakli; Gil, Susan; Lazar, Ronit; Metherate, Raju (Frontiers in Neural Circuits, 2024)
In primary auditory cortex (A1), nicotinic acetylcholine receptors (nAChRs) containing a2 subunits are expressed in layer 5 Martinotti cells (MCs)-inhibitory interneurons that send a main axon to superficial layers to inhibit distal apical dendrites of pyramidal cells (PCs). MCs also contact interneurons in supragranular layers that, in turn, inhibit PCs. Thus, MCs may regulate PCs via inhibition and disinhibition, respectively, of distal and proximal apical dendrites. Auditory inputs to PCs include thalamocortical inputs to middle layers relaying information about characteristic frequency (CF) and near-CF stimuli, and intracortical long-distance ("horizontal") projections to multiple layers carrying information about spectrally distant ("nonCF") stimuli. CF and nonCF inputs integrate to create broad frequency receptive fields (RFs). Systemic administration of nicotine activates nAChRs to "sharpen" RFs-to increase gain within a narrowed RF-resulting in enhanced responses to CF stimuli and reduced responses to nonCF stimuli. While nicotinic mechanisms to increase gain have been identified, the mechanism underlying RF narrowing is unknown. Here, we examine the role of a2 nAChRs in mice with a2 nAChR-expressing neurons labeled fluorescently, and in mice with a2 nAChRs genetically deleted. The distribution of fluorescent neurons in auditory cortex was consistent with previous studies demonstrating a2 nAChRs in layer 5 MCs, including nonpyramidal somata in layer 5 and dense processes in layer 1. We also observed label in subcortical auditory regions, including processes, but no somata, in the medial geniculate body, and both fibers and somata in the inferior colliculus. Using electrophysiological (current-source density) recordings in a2 nAChR knock-out mice, we found that systemic nicotine failed to enhance CF-evoked inputs to layer 4, suggesting a role for subcortical a2 nAChRs, and failed to reduce nonCF-evoked responses, suggesting that a2 nAChRs regulate horizontal projections to produce RF narrowing. The results support the hypothesis that a2 nAChRs function to simultaneously enhance RF gain and narrow RF breadth in A1. Notably, a similar neural circuit may recur throughout cortex and hippocampus, suggesting widespread conserved functions regulated by a2 nAChRs.